Development and Economic Benefits of Open Source Software - Simon, András (Acta Agraria Debreceniensis, 2009)
This paper discusses open source software which became one of the most important trends in the software industry recently. The most often asked questions in this area are those related to intellectual property rights. The author used a more general approach and tried to give a survey of the advantages and disadvantages that the market players (developers, government and last but not least users) have to face.After sketching the history of open source software and discussing some of the prevailing definitions, we turn out attention to the starting point: what motivates the developers? Then we give a general overview of the advantages and disadvantages of open source software. In the next part, the author analyses the software policies of the EU partially based on the abovementioned advantages and disadvantages. Finally the paper concludes with the discussion of user benefits and costs.